Leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material, preparation method and application
By preparing a flexible composite material of polyvinyl alcohol/quercetin-silver/MXene on a leather substrate, the shortcomings of existing leather-based composite materials in terms of flexibility, antibacterial properties, and sensitivity are overcome, enabling the design and development of high-performance sensors suitable for flexible wearable products and antibacterial applications.
Patent Information
- Application Number
- CN202511365665.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-23
- Publication Date
- 2026-01-09
AI Technical Summary
Existing leather-based flexible composite materials cannot simultaneously achieve flexibility, antibacterial properties, and sensitivity, making it difficult to achieve good biocompatibility and excellent antibacterial performance under mild conditions.
A method for preparing leather-based polyvinyl alcohol/quercetin-silver/MXene flexible composite materials was adopted. Through a layered infiltration-self-assembly strategy and immersion method, quercetin-silver nanoparticles, MXene nanosheets and polyvinyl alcohol were uniformly dispersed in leather to form an interpenetrating network structure. Combined with sodium chloride electrolyte as an ion-conducting material, the sensing performance and antibacterial properties were enhanced.
This technology achieves high sensitivity, wide sensing range, and excellent antibacterial properties in leather-based flexible sensors, while also improving mechanical and electrical properties, making them suitable for flexible wearable products and antibacterial applications.
Smart Images

Figure CN121294747A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of intelligent leather products and flexible wearable technology, specifically relating to a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material, its preparation method, and its application. Background Technology
[0002] In recent years, with the increasing awareness of environmental protection and health, some environmentally unfriendly synthetic polymer materials have been gradually replaced by environmentally friendly biomass materials. Biomass materials, as a renewable resource derived from living organisms, have advantages such as low cost, environmental friendliness, skin-friendliness, breathability, and good biocompatibility, and have been extensively studied as a substrate for wearable flexible sensors. Biomass-based sensors, due to their integration of the excellent properties of biomass materials and sensing elements, are an ideal choice for human health monitoring and have therefore attracted widespread attention.
[0003] Leather, as a natural wearable material, possesses excellent flexibility and mechanical strength, fully meeting the substrate material requirements of flexible sensors. Conductive hydrogels are a novel sensing material with a three-dimensional cross-linked network, excellent biocompatibility, and unique mechanical properties. Furthermore, the hydrogel's unique network structure and high hydrophilicity provide ample space for a large number of water molecules, allowing for the tunability of both its network structure and mechanical properties, thus endowing conductive hydrogels with an elastic modulus similar to human skin.
[0004] Sensors based on flexible conductive hydrogel composites with leather exhibit good compatibility with biological tissues and show great potential in simulating skin properties. In particular, their sol-gel transition characteristics allow them to be coated onto any substrate under mild conditions and adaptable to mechanical manipulation. However, current conductive hydrogels, when used as sensing materials and composited with leather, cannot simultaneously possess good flexibility, antibacterial properties, and sensitivity under mild conditions. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material, its preparation method, and its application. This invention solves the technical problem that existing leather-based flexible composite materials cannot simultaneously achieve flexibility, antibacterial properties, and sensitivity, achieving good biocompatibility and excellent antibacterial performance at a low cost and in an environmentally friendly manner.
[0006] To achieve the above objectives, the present invention employs the following technical solution: A method for preparing a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material includes the following steps: Step 1: Dissolve silver nitrate and quercetin in a mass ratio of (0.29~0.54):(0.88~1.75), adjust the pH of the resulting mixture to 7.0~7.3, and then heat it at 65~75℃. Wash and dry the resulting precipitate to obtain quercetin-silver nanoparticles. Step 2: The aqueous dispersion of quercetin-silver nanoparticles, the aqueous dispersion of MXene, and the aqueous solution of polyvinyl alcohol are sequentially infiltrated into the leather, followed by a cycle of freeze-thaw and thawing to obtain the modified leather. Step 3: The modified leather is immersed in a mixed aqueous solution of sodium chloride and polyol, and then dried to obtain a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material.
[0007] A further improvement of the present invention is that: Step 1: Dissolve silver nitrate in deionized water to obtain a silver nitrate solution. Dissolve quercetin in an aqueous ethanol solution to obtain a quercetin solution. Then, mix the two solutions in a volume ratio of (12-32):(75-153), adjust the pH of the resulting mixture to 7.0-7.3, and keep it at the specified temperature for 2-3 hours.
[0008] The MXene in step 2 is a nanosheet, obtained through the following process: Ti3AlC2 was etched in hydrofluoric acid for 24–48 h with a mass ratio of Ti3AlC2 to HF of (0.6–3.5): (8–60). The etched liquid was then centrifuged, and the resulting precipitate was washed and dried to obtain MXene nanosheets.
[0009] In step 2, the ratio of quercetin-silver nanoparticles to deionized water in the aqueous dispersion of quercetin-silver nanoparticles is (0.03-0.45) g: (10-250) mL, the concentration of MXene in the aqueous dispersion of MXene is 1-10 mg / L, and the mass percentage of polyvinyl alcohol aqueous solution is 6-10%.
[0010] Step 2 involves sequentially infiltrating the leather with an aqueous dispersion of quercetin-silver nanoparticles, an aqueous dispersion of MXene, and an aqueous solution of polyvinyl alcohol by vacuum filtration. The mass ratio of the aqueous dispersion of MXene to the aqueous solution of polyvinyl alcohol is (15.4–45.9):(63.5–126.0), and the volume ratio of the aqueous dispersion of quercetin-silver nanoparticles to the aqueous dispersion of MXene is (10–30):(10–30). The pressure is 0.080–0.098 MPa.
[0011] The cyclical freeze-thaw process described in step 2 is carried out as follows: First, freeze at -25~-20℃ for 10~14 hours, then thaw at room temperature for 2~4 hours, and then repeat the process described above 2~4 times.
[0012] The polyol mentioned in step 3 is ethylene glycol, propylene glycol or glycerol, and the mass ratio of sodium chloride, deionized water and polyol in the mixed aqueous solution is (6-35):(50-200):(10-50.2).
[0013] Step 3: Soak the modified leather in a mixed aqueous solution of sodium chloride and polyol for 12-36 hours.
[0014] A leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material prepared by the preparation method of any one of the above-described leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite materials.
[0015] Application of a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material in flexible wearable products and antibacterial applications.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: This invention discloses a method for preparing a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material. Leather is used as the flexible substrate, sodium chloride electrolyte as the ion-conducting material, and Qc-Ag and MXene as the electronically conductive materials. A layered infiltration-self-assembly strategy and immersion method are employed to prepare the leather-based flexible sensor. Its performance enhancement principle is as follows: (1) Mechanical properties: Qc-Ag particles and MXene nanosheets, as conductive fillers, are uniformly dispersed in the composite material, forming physical cross-linking points. During stretching, the interpenetrating network structure formed by the polymer network of the polyvinyl alcohol / Qc-Ag / MXene hydrogel and the interpenetrating collagen fibers, along with multiple hydrogen bonds, increases the degree of cross-linking and significantly enhances the elastic modulus. (2) Sensing performance: The sensing mechanism includes changes in the ion-conducting network generated by the electrolyte salt under external force and changes in the electronically conductive network generated by the Qc-Ag particles and MXene nanosheets. The former generates directional migration of free ions, maintaining the connectivity of the conductive path under large deformation; the latter forms an array of conductive particles and MXene nanosheets, which concentrate stress at the contact points in the micro-intervals, producing significant structural changes under small external forces, ensuring the high sensitivity of the sensor; the synergistic effect between the two can achieve high sensitivity and wide sensing range of leather-based flexible sensors, thereby improving the strain sensing ability of organic hydrogels. (3) Antibacterial properties: When in contact with bacteria, Ag NPs interact with bacteria, thereby killing them. Ag NPs can destroy the integrity of cell walls and cell membrane structures, leading to leakage of contents. At the same time, Ag NPs interact with biomolecular structures such as proteins and DNA, interfering with bacterial metabolic activities, triggering oxidative stress reactions, and ultimately leading to bacterial death. In addition, Ag NPs can release silver ions, which can also damage DNA, cell walls, proteins and lipids, achieving the purpose of antibacterial action.
[0017] This invention utilizes a layered filtration process to form a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible structure, which facilitates the formation of a three-dimensional electronic conductive network within the composite material, laying the foundation for enhanced sensor sensitivity. The leather-based composite material prepared by this method exhibits excellent mechanical, antibacterial, and conductive properties, with a wide sensing range and high sensitivity, providing new insights for the design and development of high-performance leather-based sensors. Attached Figure Description
[0018] Figure 1 Infrared spectra of leather and leather-based polyvinyl alcohol / quercetin-silver / MXene composite material of Example 1 of the present invention; Figure 2 This is a TEM image of the Qc-Ag particles in Embodiment 1 of the present invention; Figure 3SEM image of MXene nanosheets from Example 1 of this invention. Figure 4 This is a SEM image of the cross-section of the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor of Example 1 of the present invention; Figure 5 A comparison chart showing the mechanical property test results of the original leather and the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor of Example 1 of this invention; Figure 6 The curves showing the relative resistance changes of the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor prepared in Example 1 at different bending angles; Figure 7 The curves showing the relative resistance changes of the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor prepared in Example 1 at different bending frequencies are shown. Detailed Implementation
[0019] The following detailed description of the invention, in conjunction with specific embodiments, is intended to explain rather than limit the invention.
[0020] This invention discloses a method for preparing a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material, comprising the following steps: Step 1: Add a certain volume of hydrofluoric acid (40% by mass) to a plastic beaker. Weigh a certain mass of Ti3AlC2, with a Ti3AlC2 to hydrofluoric acid mass ratio of (0.6–3.5) g : (20–150) g, and gradually add it to the etching reagent in portions, stirring for 24–48 hours. After etching, the liquid is centrifuged, washed, and dried to obtain MXene nanosheets.
[0021] Step 2: Dissolve silver nitrate in deionized water to obtain a silver nitrate solution, and dissolve quercetin in a 50% (w / w) aqueous ethanol solution to obtain a quercetin solution. The volume ratio of quercetin solution to silver nitrate solution is (12-32):(75-153), and the mass ratio of quercetin to silver nitrate is (0.29-0.54):(0.88-1.75). Then, mix the two solutions and stir until uniformly dispersed. Adjust the pH to 7.0-7.3 using 1 mol / L NaOH solution, and incubate at 70℃ for 2-3 h. The resulting solid precipitate is centrifuged, washed, and dried to obtain quercetin-silver nanoparticles. Step 3: Disperse MXene nanosheets and quercetin-silver powder separately in deionized water to obtain MXene dispersion (concentration 1.0–10.0 mg / L) and Qc-Ag dispersion (Qc-Ag powder to deionized water ratio of (0.03–0.45) g: (10–250) mL); Inject the Qc-Ag dispersion, MXene dispersion, and 6–10% (w / w) polyvinyl alcohol aqueous solution sequentially into the leather via vacuum filtration at a pressure of 0.080–0.098 MPa, with the MXene dispersion to polyvinyl alcohol aqueous solution mass ratio of (15.4–45.9): (63) The volume ratio of Qc-Ag dispersion to MXene dispersion is (10~30):(10~30). The mixture is fixed in the gaps of collagen fibers inside the leather by a cyclic freeze-thaw cycle. The freezing temperature is -25~-20℃, freezing time is 10~14h, thawing time is 2~4h at room temperature, and the freeze-thaw cycle is 2~4 times. Finally, the modified leather is immersed in a mixed solution of sodium chloride, deionized water and polyol. The mass ratio of sodium chloride, deionized water and polyol is (6~35)g:(50~200)g:(10~50.2)g. The polyol is ethylene glycol, propylene glycol or glycerol. The immersion time is 12~36h. After drying, leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material is obtained. It can be used as a piezoresistive sensor in flexible wearable products and also in antibacterial applications.
[0022] Compared with the original leather, the elastic film content of the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material increased by 7.34% to 104.59%.
[0023] Example 1 Weigh 3.5 g of Ti3AlC2 and gradually add it to 150 g of 40% hydrofluoric acid using a plastic spoon, stirring for 48 hours. Centrifuge the etched black solution at 3800 r / min for 10 min, wash with water, discarding the supernatant and collecting the precipitate after each centrifugation. Continue until the pH of the supernatant from the last centrifugation is greater than 6. Obtain MXene nanosheets after vacuum drying.
[0024] 0.29 g of quercetin and 1.74 g of silver nitrate were weighed separately. Quercetin was dissolved in a 50% (w / w) aqueous ethanol solution and stirred continuously. Silver nitrate was dissolved in deionized water to obtain a silver nitrate solution. Then, the silver nitrate solution was added, and the volume ratio of quercetin solution to silver nitrate solution was 12:153. The pH was adjusted to 7.0 using 1 mol / L NaOH solution. The mixture was stirred in a 70℃ water bath for 1.5 h. The resulting composite material was centrifuged, washed, and dried to obtain quercetin-silver nanoparticles.
[0025] First, 30 mg of quercetin-silver was dispersed in 10 mL of deionized water to obtain dispersion A; 30 mg of MXene nanosheets were dispersed in 10 mL of deionized water to obtain dispersion B; 24.5 g of sodium chloride and 32.9 g of glycerol were dissolved in 120 mL of deionized water to obtain solution C; the solutions were stirred until uniformly dispersed, and then ultrasonically dispersed for 15 min. Subsequently, solutions A, B, and a 6% (w / w) polyvinyl alcohol aqueous solution were sequentially infiltrated into the leather by vacuum filtration (pressure 0.092 MPa), with a mass ratio of MXene dispersion to polyvinyl alcohol aqueous solution of 20:100. The mixture underwent four freeze-thaw cycles (freezing at -20℃ for 12 h, thawing at room temperature for 2 h) to fix its shape. Finally, it was immersed in solution C for 20 h and dried to obtain a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material.
[0026] Example 2 Weigh 1.65 g of Ti3AlC2 and gradually add it to 100 g of 40% hydrofluoric acid using a plastic spoon, stirring for 24 hours. Centrifuge the etched black solution at 3500 r / min for 5 min, wash with water, discarding the supernatant and collecting the precipitate after each centrifugation. Continue until the pH of the supernatant from the last centrifugation is greater than 6. Obtain MXene nanosheets after vacuum drying.
[0027] 0.54 g of quercetin and 0.88 g of silver nitrate were weighed separately. Quercetin was dissolved in a 50% (w / w) aqueous ethanol solution and stirred continuously. Silver nitrate was dissolved in deionized water to obtain a silver nitrate solution. Then, the silver nitrate solution was added, and the volume ratio of quercetin solution to silver nitrate solution was 20:100. The pH was adjusted to 7.3 using 1 mol / L NaOH solution. The mixture was stirred in a 70℃ water bath for 2 h. The resulting composite material was centrifuged, washed, and dried to obtain quercetin-silver nanoparticles.
[0028] First, 10 mg of quercetin-silver was dispersed in 10 mL of deionized water to obtain dispersion A; 10 mg of MXene nanosheets were dispersed in 10 mL of deionized water to obtain dispersion B; 12.9 g of sodium chloride and 21.5 g of glycerol were dissolved in 80 mL of deionized water to obtain solution C; the solutions were stirred until uniformly dispersed, and then ultrasonically dispersed for 15 min. Subsequently, solutions A, B, and 8% (w / w) polyvinyl alcohol aqueous solution were sequentially infiltrated into the leather by vacuum filtration (pressure 0.080 MPa), with a mass ratio of MXene dispersion to polyvinyl alcohol aqueous solution of 16:80. The mixture underwent three freeze-thaw cycles (freezing at -25℃ for 12 h, thawing at room temperature for 2 h) to fix its shape. Finally, it was immersed in solution C for 24 h and dried to obtain a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material.
[0029] Example 3 Weigh 2.6 g of Ti3AlC2 and gradually add it to 120 g of 40% hydrofluoric acid using a plastic spoon, stirring for 35 hours. Centrifuge the etched black solution at 4000 r / min for 5 min, wash with water, discarding the supernatant and collecting the precipitate after each centrifugation. Continue until the pH of the supernatant from the last centrifugation is greater than 6. Obtain MXene nanosheets after vacuum drying.
[0030] 0.30 g of quercetin and 1.65 g of silver nitrate were weighed separately. Quercetin was dissolved in a 50% (w / w) aqueous ethanol solution and stirred continuously. Silver nitrate was dissolved in deionized water to obtain a silver nitrate solution. Then, the silver nitrate solution was added, and the volume ratio of quercetin solution to silver nitrate solution was 15:80. The pH was adjusted to 7.0 using 1 mol / L NaOH solution. The mixture was stirred in a 70℃ water bath for 2.5 h. The resulting composite material was centrifuged, washed, and dried to obtain quercetin-silver nanoparticles.
[0031] First, 50 mg of quercetin-silver was dispersed in 30 mL of deionized water to obtain dispersion A; 60 mg of MXene nanosheets were dispersed in 30 mL of deionized water to obtain dispersion B; 30.9 g of sodium chloride and 40.2 g of glycerol were dissolved in 150 mL of deionized water to obtain solution C; the solutions were stirred until uniformly dispersed, and then ultrasonically dispersed for 15 min. Subsequently, solutions A, B, and a 10% (w / w) polyvinyl alcohol aqueous solution were sequentially infiltrated into the leather by vacuum filtration (pressure 0.098 MPa), with a mass ratio of MXene dispersion to polyvinyl alcohol aqueous solution of 45:125. The mixture underwent four freeze-thaw cycles (freezing at -22℃ for 12 h, thawing at room temperature for 2 h) to fix its shape. Finally, it was immersed in solution C for 30 h and dried to obtain a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material.
[0032] Example 4 Weigh 1.0 g of Ti3AlC2 and gradually add it to 70 g of 40% hydrofluoric acid using a plastic spoon, stirring for 24 hours. Centrifuge the etched black solution at 3000 r / min for 5 min, wash with water, discarding the supernatant and collecting the precipitate after each centrifugation. Continue until the pH of the supernatant from the last centrifugation is greater than 6. Obtain MXene nanosheets after vacuum drying.
[0033] 0.5 g of quercetin and 1.75 g of silver nitrate were weighed separately. Quercetin was dissolved in a 50% (w / w) aqueous ethanol solution and stirred continuously. Silver nitrate was dissolved in deionized water to obtain a silver nitrate solution. Then, the silver nitrate solution was added, and the volume ratio of quercetin solution to silver nitrate solution was 30:140. The pH was adjusted to 7.1 using 1 mol / L NaOH solution. The mixture was stirred in a 70℃ water bath for 1.5 h. The resulting composite material was centrifuged, washed, and dried to obtain quercetin-silver nanoparticles.
[0034] First, 45 mg of quercetin-silver was dispersed in 25 mL of deionized water to obtain dispersion A; 30 mg of MXene nanosheets were dispersed in 20 mL of PVA solution to obtain dispersion B; 25.9 g of sodium chloride and 50.2 g of glycerol were dissolved in 200 mL of deionized water to obtain solution C; the solutions were stirred until uniformly dispersed, and then ultrasonically dispersed for 15 min. Subsequently, solutions A, B, and a 9% (w / w) polyvinyl alcohol aqueous solution were sequentially infiltrated into the leather by vacuum filtration (pressure 0.090 MPa), with a mass ratio of MXene dispersion to polyvinyl alcohol aqueous solution of 35:105. The mixture underwent three freeze-thaw cycles (freezing at -20℃ for 12 h and thawing at room temperature for 2 h) to fix its shape. Finally, it was immersed in solution C for 35 h and dried to obtain a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material.
[0035] Figure 1 FTIR spectra of leather and leather-based polyvinyl alcohol / quercetin-silver / MXene composites. The characteristic absorption peaks of the leather-based flexible piezoresistive sensor in amide bands I, II, and III are 1676 cm⁻¹. -1 1569 cm -1 and 1035cm -1 The characteristic absorption peaks are the same as those of leather, indicating that the introduction of Qc-Ag, MXene, and PVA materials did not disrupt the triple-helix structure of leather collagen fibers. Furthermore, compared to leather, the characteristic absorption peak of the leather-based Qc-Ag / MXene / PVA flexible piezoresistive sensor shifted to a lower wavenumber in the amide A band to 3321 cm⁻¹, indicating that after freeze-thaw cycles, the polymer network structure of PVA formed hydrogen bonds with the collagen fibers in the leather-based flexible piezoresistive sensor.
[0036] Figure 2 The image shows a TEM image of Qc-Ag particles. The obtained nanoparticles are uniform in size and have a diameter of approximately 10 nm.
[0037] Figure 3 The image shows an SEM image of the MXene membrane, which reveals that MXene exhibits an accordion-like multilayer sheet structure. Figure 4This is a SEM image of a cross-section of a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor. Analysis of the cross-sectional SEM image reveals a hydrogel coating on the surface of the internal fibers, obscuring the original fibrous structure of the leather. The collagen fibers also exhibit a distinct hydrogel coating, and the addition of the organic hydrogel did not alter the original hierarchical structure and porosity of the leather.
[0038] Figure 5 This is a comparison of the mechanical property test results of the original leather and the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor, where s-1 and s-2 represent samples from Example 1 and Example 2, respectively. The interpenetrating network structure formed by the polymer network of the polyvinyl alcohol / Qc-Ag / MXene hydrogel and the interpenetrating collagen fibers, along with multiple hydrogen bonding interactions, resulted in increased crosslinking degree and improved elastic modulus by 104.10% and 21.15%, respectively.
[0039] Figure 6 and Figure 7 The figures show the relative resistance changes of the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible sensor under different bending angles and frequencies (bending upwards from one side). Figure 6 As shown, with the increase of the bending angle, the sensor's response electrical signal exhibits a step-like increasing trend. Figure 7 It can be seen that when the sensor is bent at different frequencies by 10°, the response electrical signal of the leather-based flexible piezoresistive sensor does not show significant increase or decrease, demonstrating good sensing capability and adaptability. When subjected to three cycles of loading and unloading at different bending angles and frequencies, the response electrical signal of the fabricated leather-based flexible sensor consistently exhibits peak values. When the sensor returns to its original state, the relative resistance change precisely returns to zero. This is because during the bending process, the large-angle stretching and compression processes lead to more significant breakage and reconstruction of conductive pathways in the three-dimensional conductive network, resulting in a larger resistance change.
Claims
1. A method for preparing a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material, characterized in that, Includes the following steps: Step 1: Dissolve silver nitrate and quercetin in a mass ratio of (0.29~0.54):(0.88~1.75), adjust the pH of the resulting mixture to 7~7.3, and then heat it at 65~75℃. Wash and dry the resulting precipitate to obtain quercetin-silver nanoparticles. Step 2: The aqueous dispersion of quercetin-silver nanoparticles, the aqueous dispersion of MXene, and the aqueous solution of polyvinyl alcohol are sequentially infiltrated into the leather, followed by a cycle of freeze-thaw and thawing to obtain the modified leather. Step 3: The modified leather is immersed in a mixed aqueous solution of sodium chloride and polyol, and then dried to obtain a leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material.
2. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 1, characterized in that, Step 1: Dissolve silver nitrate in deionized water to obtain a silver nitrate solution. Dissolve quercetin in an aqueous ethanol solution to obtain a quercetin solution. Then, mix the two solutions in a volume ratio of (12-32):(75-153), adjust the pH of the resulting mixture to 7-7.3, and keep it at the specified temperature for 2-3 hours.
3. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 1, characterized in that, The MXene in step 2 is a nanosheet, obtained through the following process: Ti3AlC2 was etched in hydrofluoric acid for 24–48 h with a mass ratio of Ti3AlC2 to HF of (0.6–3.5): (8–60). The etched liquid was then centrifuged, and the resulting precipitate was washed and dried to obtain MXene nanosheets.
4. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 1, characterized in that, In step 2, the ratio of quercetin-silver nanoparticles to deionized water in the aqueous dispersion of quercetin-silver nanoparticles is (0.03-0.45) g: (10-250) mL, the concentration of MXene in the aqueous dispersion of MXene is 1-10 mg / L, and the mass percentage of polyvinyl alcohol aqueous solution is 6-10%.
5. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 4, characterized in that, Step 2 involves sequentially infiltrating the leather with an aqueous dispersion of quercetin-silver nanoparticles, an aqueous dispersion of MXene, and an aqueous solution of polyvinyl alcohol by vacuum filtration. The mass ratio of the aqueous dispersion of MXene to the aqueous solution of polyvinyl alcohol is (15.4–45.9):(63.5–126.0), and the volume ratio of the aqueous dispersion of quercetin-silver nanoparticles to the aqueous dispersion of MXene is (10–30):(10–30). The pressure is 0.080–0.098 MPa.
6. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 1, characterized in that, The cyclical freeze-thaw process described in step 2 is carried out as follows: First, freeze at -25~-20℃ for 10~14 hours, then thaw at room temperature for 2~4 hours, and then repeat the process described above 2~4 times.
7. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 1, characterized in that, The polyol mentioned in step 3 is ethylene glycol, propylene glycol or glycerol, and the mass ratio of sodium chloride, deionized water and polyol in the mixed aqueous solution is (6-35):(50-200):(10-50.2).
8. The method for preparing the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material according to claim 1, characterized in that, Step 3: Soak the modified leather in a mixed aqueous solution of sodium chloride and polyol for 12-36 hours.
9. A leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material prepared by the method of any one of claims 1 to 8.
10. The application of the leather-based polyvinyl alcohol / quercetin-silver / MXene flexible composite material as described in claim 9 in flexible wearable products and antibacterial applications.